Capital Expenditure and Firm Performance Evidence from Albanian Construction Sector - Taipi, Ester; Ballkoci, Valbona (European Scientific Journal, ESJ, 2017)
This paper investigates the link between the capital expenditures and firm performance of Albanian firms in the construction sector, based on the data collected from 30 firms between 2008 and 2015. The study took into consideration the fact that capital expenditures is not the only variable that influences the model and as a consequence other variables affecting financial performance were analyzed, which are: leverage ratio and firm size. The linear regression model was used to analyze this relationship. According to the survey the model was explained 63% by the chosen variables. The regression analysis indicated that capital expenditures and leverage ratio are statistically significant and positively correlated with the financial performance of the firm. On the other side, the size of the firm is not a statistically significant variable and it is also negatively correlated with firm performance.